Pengaruh Kepemilikan Manajerial, Ukuran Perusahaan, Leverage, Dan Profitabilitas Pada Tax Avoidance Studi Empiris Perusahaan Manufaktur Pertambangan Yang Terdaftar Di BEI Pada Tahun 2019-2023 - Sintya Dewi, Dewa Ayu; Indraswarawati, Sang Ayu Putu Arie; Yuniasih, Ni Wayan (UNHI Press, 2025)
The population used is mining manufacturing issuers in 2019-2023. From the criteria used, a sample of 18 companies was obtained. Data collection was carried out by conducting documentation studies of company financial reports and analysis using regression equations. Based on the results of the research and discussion that have been presented, it can be concluded that the managerial ownership company size and profitability have a positive effect on tax avoidance while leverage have no effect on tax avoidance mining manufacturing companies on the IDX in 2019-2023